Vices-paradox in trauma: Positive alcohol and drug screens associated with decreased mortality. (1st September 2021) - Covarrubias, Jose; Grigorian, Areg; Nahmias, Jeffry; Chin, Theresa Lynn; Schubl, Sebastian; Joe, Victor; Lekawa, Michael
Highlights: Trauma patients with substance use have a higher incidence of traumatic injury. However, there is an apparent paradoxical association between substance use and mortality. Alcohol, illegal or controlled substance use has a 12 %, 17 %, and 28 % decreased odds of mortality, respectively. Abstract: Background: Improved survival in trauma patients with acute alcohol intoxication has been previously reported. The effect of illegal and controlled substances on mortality is less clear. We hypothesized that alcohol, illegal and controlled substances are each independently associated with lower odds of mortality in adult trauma patients. Methods: The Trauma Quality Improvement Program (2010–2016) was queried for patients screening positive for alcohol, illegal or controlled substances on admission. A multivariate logistic regression analysis was used to determine odds of mortality. A similar analysis was used after stratification by injury severity scale (ISS). Results: From 1, 299, 705 adult patients, 660, 135 were screened for substance use. Of these patients, 497, 872 were male, 227, 995 (34.5 %) screened positive for alcohol, 155, 437 (23.5 %) for illegal substances and 90, 259 (13.7 %) for controlled substances. Mortality rate was 6.2 % with alcohol, 5.1 % with illegal substances, and 5.7 % with controlled substances compared to 8.0 % with no substance use (p < 0.001). After controlling for covariates, all groups had lower odds of mortality: alcohol (OR = 0.88, CI = 0.84−0.92, p < 0.001), illegal substances (OR = 0.83, CI = 0.77−0.90, p < 0.001), controlled substances (OR = 0.72, CI = 0.67−0.79, p < 0.001). When stratified by ISS, alcohol and illegal substances continued to be associated with decreased mortality until ISS 50. Controlled substances were associated with decreased mortality when ISS > 16. Conclusion: Patients positive for alcohol, illegal or controlled substances have 12 %, 17 %, and 28 % decreased odds of mortality, respectively. This paradoxical association should be confirmed with future clinical studies and merits basic science research to identify biochemical or physiological components conferring a protective effect on survival in trauma patients.